Interpreting the behavior of concentration–response curves of hyaluronidase inhibitors under DMSO-perturbed assay conditions. Issue 13 (1st July 2016) - Tomohara, Keisuke; Ito, Tomohiro; Onikata, Saika; Furusawa, Kota; Kato, Atsushi; Adachi, Isao
Graphical abstract: Abstract: Hyaluronan-degrading enzyme (hyaluronidase) is involved in tumor growth and inflammation, and as such, hyaluronidase inhibitors have received recent attention as potential therapeutics. The previous studies have successfully discovered a wide range of inhibitors, but unfortunately most of them are dissimilar to original ligand hyaluronan and the mode of action is poorly understood. The present study mechanistically characterized these structurally unrelated inhibitors by interpreting the behavior of concentration–response curves under several in vitro assay conditions. Detergent-addition conditions definitely identified aggregation-based inhibitors. Subsequently, DMSO-perturbed conditions, though preliminary, highlighted the inhibitors that might bind to enzyme non-specifically. Here, an intriguing implication of the latter description is that DMSO-perturbed conditions would generate non-productive but not-denatured enzyme that is an assembly of effective species to capture non-specific binding molecules, and thereby would attenuate their inhibitory activities.